PENGARUH FINANCING TO DEPOSIT RATIO (FDR) DAN NON PERFORMING FINANCING (NPF) TERHADAP RETURN ON ASSET (ROA) (Studi Pada di Bank Syariah Mandiri Periode 2012-2019) - Nurandika Maulana Rachman; Rully Trihantana; Ria kusumaningrum (SAHID BANKING JOURNAL, 2021)
ABSTRACT Bank Indonesia in BI Circular Letter No. 9/24/DPbs 2007 states that the assessment of the soundness of a bank is influenced by the CAMELS factor (Capital, Asset Quality, Management, Earnings, Liquidity, Sensitivity to Market Risk). This study aims to examine the effect of Financing to Deposit Ratio (FDR) and Non Performing Financing (NPF) on Return On Assets (ROA) at PT. Mandiri Syariah Bank for the 2012-2019 period. The research method used is the type of quantitative and secondary data from the financial statements of PT. Bank Syariah Mandiri starting from the first quarter of 2012 to the fourth quarter of the 2019 period so that 32 samples of financial statements were collected. Based on the results of the study, it shows that the Financing to Deposit Ratio (FDR) and Non Performing Financing (NPF) simultaneously have a significant effect on Return On Assets (ROA), with a Fcount of 110.076 > Ftable of 4.17 and a significance of 0.000 <0.05, the results the coefficient of determination for the Adjusted R Square (R2) value is 0.876 or 87.6%, which means that Return on Assets (ROA) can be influenced by both variables, namely Financing to Deposit Ratio (FDR) and Non Performing Financing (NPF). While the remaining 12.4% is influenced by other factors outside the research model.